Analisis Etika Bisnis dan Tata Kelola Perusahaan Startup dalam Skandal Keuangan - Halimah Zahrah; Andika Amirudin; Hoerul Dwi Natya Fauzan; Firyal Adilah Tisan (Indonesia Economic Journal, 2025)
This research explores ethical misconduct and corporate governance shortcomings in the financial controversy surrounding eFishery, an influential agritech startup in Indonesia. The country’s rapid digital expansion and investor-focused startup ecosystem have raised questions about organizational integrity and sustainability. The study focuses on identifying the tensions between valuation-driven growth and the adoption of ethical standards and governance principles. A qualitative literature review was conducted using materials from 2024 to 2025, including academic literature, regulatory data, media investigations, and company disclosures. Analysis draws on agency theory, stakeholder theory, and normative ethical frameworks to interpret the behavioral and structural violations involved. Findings reveal unethical practices, such as distorted financial records, misleading use of user data, and opacity in distributing support to aquaculture stakeholders. The company failed to meet the expectations of Good Corporate Governance, particularly in transparency, accountability, independence, and fairness. Recommendations proposed involve instituting whistleblowing systems, restructuring incentive mechanisms, cultivating moral awareness in organizational culture, and involving stakeholders in decision-making processes. The case of eFishery demonstrates the damaging consequences of ethical neglect and governance breakdown. Long-term resilience in startups within emerging economies demands early integration of ethical governance values.